XopR, a Type III Effector Secreted by Xanthomonas oryzae pv. oryzae, Suppresses Microbe-Associated Molecular Pattern-Triggered Immunity in Arabidopsis thaliana - Chiharu Akimoto-Tomiyama; Ayako Furutani; Seiji Tsuge; Erica J. Washington; Yoko Nishizawa; Eiichi Minami; Hirokazu Ochiai (Molecular Plant-Microbe Interactions, 2012)
Xanthomonas oryzae pv. oryzae is the causal agent of bacterial blight of rice. The XopR protein, secreted into plant cells through the type III secretion apparatus, is widely conserved in xanthomonads and is predicted to play important roles in bacterial pathogenicity. Here, we examined the function of XopR by constructing transgenic Arabidopsis thaliana plants expressing it under control of the dexamethasone (DEX)-inducible promoter. In the transgenic plants treated with DEX, slightly delayed growth and variegation on leaves were observed. Induction of four microbe-associated molecular pattern (MAMP)-specific early-defense genes by a nonpathogenic X. campestris pv. campestris hrcC deletion mutant were strongly suppressed in the XopR-expressing plants. XopR expression also reduced the deposition of callose, an immune response induced by flg22. When transiently expressed in Nicotiana benthamiana, a XopR::Citrine fusion gene product localized to the plasma membrane. The deletion of XopR in X. oryzae pv. oryzae resulted in reduced pathogenicity on host rice plants. Collectively, these results suggest that XopR inhibits basal defense responses in plants rapidly after MAMP recognition.